Design of Hybrid Controller by Fuzzy Sliding Mode for an Induction Motor, ISSN 2328-2223 - Bendaas Ismail; Naceri Farid (Revue des Sciences et de la Technologie - RST, 2014)
This paper presents a synthesis of two control strategies, sliding mode (SMC) and hybrid fuzzy sliding mode control (FSMC) for application to an induction motor (IM) for more precisely, present a performance of fuzzy sliding mode control. To solve those problems associated with conventional control by sliding mode,such as high current, flux and torque chattering, variable switching fr e q u e n c y . Meanwhile, the design of a hybrid controller based on fuzzy sliding mode control (FSMC) is proposed, in which a fuzzy logic controller replaces the discontinuous part of the classical sliding mode control law. Simulations results of the proposed control theme present good dynamic and steady-state performances as compared to the classical SMC from aspects of the reduction of the torque chattering, the quickly dynamic torque response and robustness to disturbance.